2022
DOI: 10.1007/s11162-022-09675-x
|View full text |Cite
|
Sign up to set email alerts
|

You are Admitted! Early Evidence on Enrollment from Idaho’s Direct Admissions System

Abstract: In 2015, Idaho adopted the nation’s first direct admissions system and proactively admitted all high school graduates to a set of public institutions. This reimagination of the admissions process may reduce barriers to students’ enrollment and improve access across geographic and socioeconomic contexts by removing many human capital, informational, and financial barriers in the college search and application process. Despite a lack of evidence on the efficacy of direct admissions systems, the policy has alread… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 84 publications
0
4
0
Order By: Relevance
“…Similar to the model of preapproving customers in consumer markets, direct admissions policies make proactive admissions offers to high school students that meet admissions criteria. Odle and Delaney (2022) found that adoption by Idaho increased first-time undergraduate enrollment at the campus level and the state level. Five states have adopted direct admissions or are considering adoption (Odle & Delaney, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to the model of preapproving customers in consumer markets, direct admissions policies make proactive admissions offers to high school students that meet admissions criteria. Odle and Delaney (2022) found that adoption by Idaho increased first-time undergraduate enrollment at the campus level and the state level. Five states have adopted direct admissions or are considering adoption (Odle & Delaney, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Odle and Delaney (2022) found that adoption by Idaho increased first-time undergraduate enrollment at the campus level and the state level. Five states have adopted direct admissions or are considering adoption (Odle & Delaney, 2022). Brown and Burns (2023) state that identifying eligible students and their contact information is a significant barrier to equality of opportunity in direct admissions.…”
Section: Discussionmentioning
confidence: 99%
“…Ultimately, high schools are a key place to help resolve these differences, as efforts to reach undocumented students must begin earlier in the application process to help them choose the postsecondary environment that will maximize their chances of success. Alternately, colleges or states can engage in more targeted policies that simplify and provide clarity to admissions processes, which have been shown to increase enrollment (Dynarski et al, 2021; Odle & Delaney, 2022). It is a smaller point, but these results also highlight the importance of better microdata, as we provide a more complicated narrative of differences in CSU and UC college enrollment rather than one that simply examines the choice between 2- and 4-year colleges.…”
Section: Discussionmentioning
confidence: 99%
“…The point estimates from our main results are substantively unchanged, although the standard errors for these lagged estimates are large, given fewer posttreatment years. For all estimates, we cluster standard errors at the state (treatment) level to control serial correlation in outcomes (Cameron & Miller, 2015), particularly given the salience of state policy and geography in shaping outcomes for students and institutions (González Canché, 2014, 2017, 2018; Odle, 2021; Odle & Delaney, 2022; Odle & Monday, 2021).…”
Section: Empirical Strategymentioning
confidence: 99%